Interaction ritual chains. - Collins, Randall, 1941- (Princeton studies in cultural sociology., 2004)
Sex, smoking, and social stratification are three very different social phenomena. And yet, argues sociologist Randall Collins, they and much else in our social lives are driven by a common force: interaction rituals. Interaction Ritual Chains is a major work of sociological theory that attempts to develop a ""radical microsociology."" It proposes that successful rituals create symbols of group membership and pump up individuals with emotional energy, while failed rituals drain emotional energy. Each person flows from situation to situation, drawn to those interactions where their cultural ca.